HUBUNGAN ANTARA KEADILAN ORGANISASI DAN PERSEPSI DUKUNGAN ORGANISASI DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) GURU DI SMP NEGERI SE-KECAMATAN DUREN SAWIT - Fitri Mardiyanti; Desi Rahmawati (Program Studi Manajemen Pendidikan, 2017)
This research aims to determine whether there is a relationship between organizational justice and perceived organizational support (POS) with teacher’s organizational citizenship behavior (OCB) on Junior High School in The Duren Sawit Sub District, Jakarta City. This research is quantitative with three variables there in, namely: (X) organizational justice and perceived organizational support (POS) as independent variables and (Y) organizational citizenship behavior (OCB) as the dependent variable. The research using survey method and analyzed data with correlation and regression. The result of the research showed that: (1) there is a positive correlation between organizational justice with organizational citizenship behavior (OCB) (2) there is a positive correlation between perceived organizational support (POS) with organizational citizenship behavior (OCB), and (3) there is a positive correlation between organization justice and percieved organizational support (POS) with organizational citizenship behavior (OCB). Keywords: organizational justice, perceived organizational support, organizational citizenship behavior